Trichogramma pretiosum (Hymenoptera: Trichogrammatidae): desenvolvimento em ovos de populações resistentes de Plutella xylostella (Lepidoptera: Plutellidae) e seletividade à produtos fitossanitários isoladamente ou em misturas compatíveis - Teixeira, Camila Santos (2020)
The control integration methods demands knowledge about different aspects of bioecology of the involved organisms. The objective was to evaluate the performance of Trichogramma pretiosum Riley (Hymenoptera: Trichogrammatidae) over Plutella xylostella (L.) (Lepidoptera: Plutellidae) eggs from insecticide resistant populations as well as evaluate the different phytosanitary products in mixture and it is selectivity to parasitoids. The experiments was conducted in “Laboratório de Entomologia Aplicada (LEA - UFC) ”, Fortaleza, Ceará State, Brazil. In essays with P. xylostella, cards containing six eggs of five populations (SUS, D-Delta, D-Bt, D-controle, D-rotação) up to 24 hours old were inserted in glass tubes (8,5 x 2,5 cm) containing one just emerged female of T. pretiosum and kept at 25 ± 2º C, 70 ± 10% R.M. and 12 hours photophase until adults emergence. The main biological parameters related to the parasitoid were evaluated. For the first phytosanitary products mixture test were prepared spray solutions containing: Chlorantraniliprole, metaflumizone, Bacillus thuringiensis, thiamethoxam, espinosade, cyantraniliprole, imidacloprid, chlorfenapyr and tebuconazole + trifloxystrobin with the manufacturer recommended dose. It utilized distilled water with pH 6,0 in the control and in spray solutions’ preparation. In the second test, it was made cards containing 10 eggs from Anagasta kuehniella (Zeller) (Lepidoptera: Pyralidae) up to 24 hours old, immersed for 5 seconds in the individual spray solutions and in the mixtures (M1= chlorantraniliprole + metaflumizone + BT; and M2= chlorantraniliprole + chlorfenapyr + BT), and in distilled water (control), been inserted in glass tubes containing one T. pretiosum female for 24 hours, characterizing pre-parasitism. For post-parasitism tests, cards immersion in the spray solutions were realized 24 and 168 h after parasitism. T. pretiosum was capable of developing in resistant populations’ eggs of P. xylostella showing parasitism over 65%. The mixtures did not show physical alterations, but WG formulations sedimented after 10 minutes. The mixture M1 showed selectivity to T. pretiosum in the post-parasitism test, in egg and pupae phases, it was considered innocuous. Chlorantraniliprole and metaflumizone were innocuous (selectives) to T. pretiosum. The parasitoids’ number per egg and sexual ratio of T. pretiosum were not altered for the phytosanitary products applications singly or in mixture.